Repercussion of financial distress and corporate disclosure on the valuation of non-financial firms in India - Venkata Mrudula Bhimavarapu; Shailesh Rastogi; Jagjeevan Kanoujiya; Aashi Rawal (Future Business Journal)
Abstract Distressed companies create panic among the investors, and the overall effect comes on the economy and leads to a degraded image and value of the companies. Transparency and disclosure involve disclosing the operational as well as the financial performance and corporate governance practices employed by the firms. A corporation or person is said to be in a financial distress (FD) if they are unable to keep their pledge to make payments on time. The current study seeks to shed light on the effects of Financial Distress (FD) and Transparency and Disclosure (T&D) on the value of non-financial firms operating in India. The study makes use of panel data analysis (PDA). The authors of the study used secondary data of non-financial companies included in the S&P BSE 100 index for five fiscal years, from 2015–2016 to 2019–2020. Altman Zscore for FD measure and Tobin's Q, MCAP, and MTB for the firm's valuation is considered. Our study established that Financial Distress (FD) negatively impacts a firm's valuation because a positive association between Zscore (financial soundness) and a firm's value is found. However, Transparency and Disclosure (T&D) have no significant impact on the firm’s valuation. We also find evidence that financial distress significantly impacts the value of firms under the influence of T&D. With the help of information about financial distress provided in our study, companies can analyze and take required steps to minimize the probability of being in a state of insolvency or being bankrupt. Investors can also gain knowledge of the business factors and their effect on a company's valuation so that they can cautiously choose and include healthy companies in their targeted list of companies to invest in. No such study has been conducted till now in any of the developing countries that include finding the impact that (FD) as well as (T&D) have on the value of the firms in the non-financial sector.